Nilai Yang Dipersepsikan Terhadap Kepuasan Pelanggan Serta Dampaknya pada Loyalitas Pelanggan Industri Jasa Perbankan di Kota Denpasar - Ni Luh Sayang Telagawathi (Ekuitas: Jurnal Pendidikan Ekonomi, 2019)
As the developing of the research made by Anderson, et al. (1996); primary purpose of the research reported here is to observe empirically several specific hypothesis influence of customer expectation, perceived quality, perceived value, customer satisfaction, customer complaint and customer loyalty in bank service. The result this study show that customer satisfaction directly affected by perceived quality and perceived value postpurchase. Perceived value itself is affected by perceived quality and customer expectation. Customer expectation not directly affected by customer satisfaction but customer expectation indirectly affected by perceived value.  Research also found that consistency of customer satisfaction  do not give any influence to customer complaint but customer satisfaction in banking service industry has a significant influence by customer loyalty. The results of the research is aimed to explain the existing of relationship between customer expectation, perceived quality, perceived value of customer satisfaction and  relationship between customer satisfaction to customer loyalty. The concept implied on this research will help much in resolving problem and decision making based on to service marketing development program, and implement the best quality strategy as the key to service provider effort the position themselves more effectively in the market place. Respondent is 200 customers of Mandiri in Denpasar. Two-Step Approach to Structural Equation Model (SEM).